Constructivist and Social Constructionist Career Counseling: A Delphi Study. Issue 1 (March 2017) - Kang, ZiYoung; Kim, Hyunhee; Trusty, Jerry
Abstract : Constructivist and social constructionist (SC) career counseling approaches direct attention to individuals as authors who construct their identities and careers in relation with others. Often contrasted with positivist or modern approaches, distinguishing features of these relatively new approaches have not yet been explicitly identified. Panel members in this Delphi study comprised the 9 most‐cited authors on the topics of constructivist and SC career counseling, 8 of whom completed all 3 rounds of questionnaires. They offered views about definitions of constructivist and SC career counseling and identified distinguishing and essential features of these approaches in terms of theoretical underpinnings, counseling processes, client–counselor relationships, and range of applicability. The defining features and the range of applicability identified in this study may serve to guide practice, training, and supervision. A research agenda including development of fidelity measures and evaluation of the efficacy of these approaches is proposed. Controversial issues are discussed.